INFLUENCE OF LONG-TERM USE OF ANTIHYPERTENSIVE DRUGS AND THE "HYPERTENSION SCHOOL" ON THE DEVELOPMENT OF THE RISK OF CARDIOVASCULAR COMPLICATIONS IN PATIENTS WITH ARTERIAL HYPERTENSION - Dilfuza Z. Yarmukhamedova; Nigora B. Nuritdinova (Central Asian Journal of Medicine, 2023)
Purpose of the study. To study the effectiveness of long-term antihypertensive therapy and the impact of the educational program "School of hypertension" on the incidence of cardiovascular complications in patients with AH (arterial hypertension) I-II degree in a polyclinic. Material and research methods. The study included 610 patients with 1–2-degree AH. The duration of AH was 6.8±1.6 years. Of the 610 patients examined, 231 (37.9%) were patients with stage I AH (mean age of patients was 46.7 ± 7.0 years) and 379 (62.1%) with stage 2 AH (mean age 49.1 +6.92 years).